Významnost (materialita) a její vnímání uživateli účetních informací; empirický výzkum - Novotný, Ota; Králíček, Vladimír, 1952-; Šindelář, Michal; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
Audit materiality is often initially assessed using 'rules of thumb'—general benchmarks derived from historical professional experience and industry standards. Given its foundational role in ensuring auditors provide meaningful service to stakeholders, understanding the perceptions of financial statement users regarding materiality is critical. Building on Vance's (2022) meta-analysis, which reviewed five decades of empirical research, this study introduces an innovative approach to examining materiality by analysing indemnity basket clauses in Share Purchase Agreements (SPAs). Using a dataset of 72 transactions involving target companies in the Czech Republic between 2014 and 2024, sourced from the Capital IQ database and the public Commercial Register, this research examines the relationship between transaction values and materiality thresholds. The analysis reveals that indemnity basket clauses set at 0.5% and 1% of total transaction value correspond to mean thresholds of 9.2% and 18.4% of Earnings After Tax (EAT), respectively, significantly exceeding the 7.85% mean materiality identified for auditors in Vance's (2022) meta-analysis. This indicates that auditors work with a higher level of detail. Additionally, this study successfully rejects the null hypothesis when comparing results for the 0.5% basket to Vance's findings for investors and analysts, suggesting that this research design offers a promising framework for future studies. While grounded in prior practical law studies on indemnity clauses and materiality ranges, this research introduces a novel methodology for integrating investor-focused materiality perceptions into broader meta-analyses. By drawing on a field that is often overlooked in academic economics, this study offers a fresh perspective on materiality thresholds and their broader implications for both auditors and investors.
Vedoucí práce: Vladimír Králíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor dipl. práce]; diplomové práce; master's theses